(untitled) (Open Academia: Journal of Scholarly Research, 2025)
Lexico-semantic relations represent a fundamental component of linguistic structure, shaping communication, conceptual categorization, and lexicographic practice. Within the Uzbek language, these relations form intricate semantic networks linking lexical units through meaning similarity, hierarchical relations, functional connections, and degree-based differences. In particular, the interpretation of synonymy and semantic gradation has considerable importance due to their centrality in structuring lexical paradigms and shaping the explanatory mechanisms employed in dictionaries. The present article explores how such relations are represented in lexicography and identifies principles essential for developing lexicographic models that accurately reveal semantic hierarchy, lexical nuance, and contextual characteristics. Drawing on system-structural linguistics, semantic field theory, and semebased analysis, this work proposes a refined approach to defining and organizing lexical units. The study emphasizes the need for lexicographic entries that systematically articulate general meaning, distinctive semantic features, illustrative evidence, and degree markers. Recommendations offered in this work aim to strengthen the semantic precision and descriptive value of dictionaries within Uzbek linguistics and contribute to the advancement of lexicographic methodology